Pemberian Terapi Angle Pump Exercise Dan Elevasi 30⁰ Untuk Mengurangi Edema Pada Pasien CKD - Sertin Oktavia Maro; Yuliani Pitang (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Chronic Kidney Disease (CKD) is a condition in which kidney function decreases so that it is no longer able to filtrate the body's metabolic waste and maintain electrolyte fluid balance. In CKD an increased amount of fluid can result in edema. Edema is a condition of blocked veins due to an increase in intravascular hydrostatic pressure that causes enlargement or buildup of plasma fluid into the interstitium space. Therapy that can be applied to reduce edema in CKD is with Ankle Pump Exercise and Elevation 30⁰. This therapy is done by pumping the ankle and elevating the foot for 5-10 minutes. The goal of this study was to identify Ankle Pump Exercise and 30⁰ Elevation interventions to reduce edema in CKD patients in the ICU. The type / research design used is a descriptive method with a case study approach. The subjects of this case study were patients who met the inclusion criteria, namely patients with edema and were willing to be respondents. The data collection instrument uses the format of Nursing Care. The results of this study showed that Ankle Pump Exercise and 30⁰ Elevation interventions effectively reduced edema in CKD patients. Based on the results of the case study, it can be concluded that the application of a combination therapy of ankle pump exercise and 30⁰ foot elevais has been proven effective in reducing the degree of edema in Chronic Kidney Disease (CKD) patients.